Empowerment Of Village Communities In Forest Areas Assisted By Perum Perhutani KPH Mojokerto: Socialization Of Corn Processing Into Drinks As A Productive Business - ElviEsya Ananta; Yani Evi Asih; Fatma Nurmala Sari; Fazlul Rahman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The forest village communities assisted by Perum Perhutani KPH Mojokerto generally only sell corn in raw form, so the added value obtained is still relatively low. This encourages the need for innovation in processing corn into high-value products as an effort to empower and improve the welfare of forest village communities. This community service activity aims to increase community knowledge and skills in processing corn into an innovative drink called Corn Forest Drink as a sustainable productive business. The method used includes three stages, namely the pre-activity stage in the form of product trials and material preparation, the implementation stage in the form of socialization and demonstration of product making through video screenings, and the evaluation stage through a question-and-answer session. The activity was carried out on May 8, 2026, in Jatipandak Village, Sambeng District, Lamongan Regency with LMDH Jati Mulya assisted by Perum Perhutani KPH Mojokerto. The results of the activity showed that all participants gave a very positive response to the Corn Forest Drink product, both in terms of taste, appearance, and its economic potential. The processing process is considered simple and can be done using household equipment already owned by the community. This innovation has been proven to significantly increase the selling value of corn and open up productive business opportunities for forest village communities. This community service activity concluded that processing corn into Corn Forest Drink is an innovative and effective solution for encouraging economic empowerment of forest village communities based on local potential.